Analisis Keuntungan Produk Olahan Kacang Mete Skala Rumah Tangga - Navita Maharani (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
Cashew nuts are one of the agricultural commodities that is primarily consumed as a producer of raw materials for industry (Basuki, 2005). Cashew nut (Anancardium occidentalle L) is a long-lived crop with high economic value. Karangnongko Hamlet is a cashew production center in Sumberagung Plosloklaten Kediri Village. The cashew processing business ready for consumption is currently not widely developed in Sumberagung Village. Farmers only sell cashew logs (untreated and separated from the shell). Cashew can be processed on a small-scale basis at home to increase the product's value and selling price. The purpose of this study is to identify the benefits of processed cashew products on a household level. The methods used include cost analysis, Break Even Point, and R/C Ratio analysis. The results showed that household-scale cashew processed products are profitable and feasible to run with an R/C Ratio value 1.44. Product marketing is also carried out through online media and e-commerce. This effort was made to increase the added value and selling price of cashew products as well as the income of the local community.